ANALISIS PENGARUH E-READINESS FACTORS TERHADAP INTENSI UKM ADOPSI E-BUSINESS - Titik Kusmantini (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
Today’s market and competitive pressure companies to adopt internet-based electronic business (e-business), neverless Small and Medium Enterprises (SME’s). In this study to examines a conceptual model for electronic business adoption based on the technology-organization-environment framework. Survey methode is applied in this research and the sample quantity is 67 SME’s that produce are silk handycraft, terracota handycraft, textile, furniture, Mozaik stone, silver handycraft and batik fashion and this product as icon or jargon product on Yogyakarta. The Technique of sample drawing used is method of purposive sampling with criteria selection are SME’s have export-oriented mission. This research applies statistical technique of simple regression. The conclusion of all the hypoteses proposed are: (1) there are influences technology competence to intens-to adopt e-business; (2) there are influances organization readiness to intens-to adopt e-business; (3)there are no influences consumer readiness to intens-to adopt e-business; (4) there are influences competitive pressure to intens-to adopt e-business and (5) there are no influences lack of trading partner readiness to intens-to adopt e-business.